Call your daughter home - Spera, Deb (Park Row Books, 2019)
"It's 1924 South Carolina and the region is still recovering from the infamous boll weevil infestation that devastated the land and the economy. Gertrude, a mother of four, must make an unconscionable decision to save her daughters from starvation or die at the hands of an abusive husband. Retta is navigating a harsh world as a first-generation freed slave, still employed by the Coles, influential plantation proprietors who once owned her family. Annie is the matriarch of the Coles family and must come to terms with the terrible truth that has ripped her family apart. These three women seemingly have nothing in common, yet as they unite to stand up to the terrible injustices that have long plagued the small town, they find strength in the bond that ties women together."--Publisher's description.